Modelado de la sismicidad colombiana como una red compleja espacio-secuencial - León-Vargas, Daniel; Bucheli-Guerrero, Víctor-Andrés; Ordoñez-Erazo, Hugo-Armando (Revista Científica, 2023)
This article seeks to describe the seismicity of Colombia using complex networks, in which the nodes represent cubic cells (with latitude, longitude, and depth) where seismic events occur, and the links follow the temporal sequence of these events. While similar works have been reported in the literature, this study incorporates depth to gain a more detailed understanding of this phenomenon. This research considers 5797 events from the earthquake catalog of the United States Geological Survey (USGS), corresponding to Colombia and with a magnitude greater than a certain threshold, which occurred between January 1, 1975, and January 18, 2021. The network structure is described by comparing random and small-world networks. Thus, said structure provides information about the energy release mechanisms and the sources that recurrently produce seismic events in Colombia. The results show that these networks exhibit small-world properties, regardless of the cell size or granularity used to construct them. This finding is consistent with the results reported for the same region in two-dimensional spatiotemporal networks. As a small-world network, the effort and energy in the region are released according to a structure represented by the presence of hubs and their relationships within the overall network. By leveraging the information obtained in this study, it is possible to train machine learning models that outperform the current baseline forecasting models.